On-surface assembly of hydrogen- and halogen-bonded supramolecular graphyne-like networks - Yang, Zechao; Fromm, Lukas; Sander, Tim; Gebhardt, Julian; Schaub, Tobias A.; Görling, Andreas; Kivala, Milan; Maier, Sabine (Angewandte Chemie. International edition, 2020)
Demonstrated here is a supramolecular approach to fabricate highly ordered monolayered hydrogen- and halogen-bonded graphyne-like two-dimensional (2D) materials from triethynyltriazine derivatives on Au(111) and Ag(111). The 2D networks are stabilized by N⋅⋅⋅H−C(sp) bonds and N⋅⋅⋅Br−C(sp) bonds to the triazine core. The structural properties and the binding energies of the supramolecular graphynes have been investigated by scanning tunneling microscopy in combination with density-functional theory calculations. It is revealed that the N⋅⋅⋅Br−C(sp) bonds lead to significantly stronger bonded networks compared to the hydrogen-bonded networks. A systematic analysis of the binding energies of triethynyltriazine and triethynylbenzene derivatives further demonstrates that the X3-synthon, which is commonly observed for bromobenzene derivatives, is weaker than the X6-synthon for our bromotriethynyl derivatives.
First published: 03 March 2020
Gesehen am 26.09.2022